Behavioral problems in people with intellectual disability: Basic facts, incidence and risk factors - Buha Nataša; Gligorović Milica (Specijalna Edukacija i Rehabilitacija, 2013)
In people with intellectual disabilities, behavioral problems result from the interaction of multiple risk factors of different origin, which undoubtedly indicates the importance of knowing their individual characteristics and life circumstances. Incidence, specific forms and topography of behavioral problems depend on different factors, both socio-demographic and inherent ones. Behavioral problems significantly impede acquiring new adaptive skills and have a negative influence on the interaction with the environment. Emotional and behavioral problems are a significant source of stress in children with intellectual disability, as well as their parents and professional staff. These difficulties, especially aggression and disruptiveness, have a big influence on the selection of education model, i.e. on how much the child will be involved in the educational process and the decision whether or not a person will be institutionalized. Better understanding of behavioral problems in people with intellectual disability is the basis of eliminating or reducing risk factors, as well as creating a comprehensive treatment model.